Trigeminal autonomic cephalalgias. (8th August 2014) - Eller, M; Goadsby, PJ
Abstract : The trigeminal autonomic cephalalgias (TACs) are a group of primary headache disorders characterised by lateralized symptoms: prominent headache and ipsilateral cranial autonomic features, such as conjunctival injection, lacrimation and rhinorrhea. The TACs are: cluster headache (CH), paroxysmal hemicrania (PH), short‐lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT)/short‐lasting neuralgiform headache attacks with cranial autonomic features (SUNA) and hemicrania continua (HC). Their diagnostic criteria are outlined in the International Classification of Headache Disorders, third edition‐beta (ICHD‐IIIb). These conditions are distinguished by their attack duration and frequency, as well as response to treatment. HC is continuous and by definition responsive to indomethacin. The main differential when considering this headache is chronic migraine. Other TACs are remarkable for their short duration and must be distinguished from other short‐lasting painful conditions, such as trigeminal neuralgia and primary stabbing headache. Cluster headache is characterised by exquisitely painful attacks that occur in discrete episodes lasting 15–180 min a few times a day. In comparison, PH occurs more frequently and is of shorter duration, and like HC is responsive to indomethacin. SUNCT/SUNA is the shortest duration and highest frequency TAC; attacks can occur over a hundred times every day.